ANALISIS PENGARUH FRAUD DIAMOND DALAM MENDETEKSI TINGKAT ACCOUNTING IRREGULARITIES - Zulvi Nurbaiti; Rustam Hanafi (Jurnal Akuntansi Indonesia, 2017)
This study aimed to analyze the factors that effect the level of accounting irregularities. Accounting Irregularities isthe aggresive accounting practices, misuse of the facts that apply to the financial statements either intentionallyor unintentionally, omission or misinterpretation of accounting standarts, and fraud. The variables of thr frauddiamond that used is pressure, opportunity, rationalozation and capability. The population in this study is the nonfinancialcompanies listed in Indonesia Stock Exchange in 2012-2014 and the sampling technique is purposivesampling. The type of data used are secondary data from Indonesia Stock Exchange in the form of financialstatement. Total sample of this study is 81 non financial companies, that perform restatement during 2012 until2014. This research used logistic regression analysis to test the hypothesis. The result of this study indicate thatrationalization has positif significant effect on the level of accounting irregularities. While the pressure, opportunityand capability had no significant effect on the level of accounting irregularities.Keywords : Accounting Irregularities, Fraud,Fraud Diamond, Financial Restatement